A new unsymmetrical near-IR small molecule with squaraine chromophore for solution processed bulk heterojunction solar cells. Issue 27 (12th June 2015) - Paek, Sanghyun; Choi, Hyeju; Jo, Hyunjun; Lee, Kiae; Song, Kihyung; Siddiqui, S. A.; Sharma, G. D.; Ko, Jaejung
Abstract : A new unsymmetrical low bandgap push–pull squaraine chromophore bis-DMFA-Th-SQ-Th-DCA (JK216D ) was synthesized and its optical and electrochemical properties were investigated. Abstract : A new unsymmetrical low bandgap push–pull squaraine chromophore bis-DMFA-Th-SQ-Th-DCA denoted asJK216D was synthesized and its optical and electrochemical properties (both theoretical and experimental) were investigated. This small molecule having a strong electron withdrawing moiety exhibits a broader absorption band in thin film. TheJK216D exhibited suitable highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital energy levels, compatible with that of PC71 BM, for efficient photoinduced electron transfer. The bulk heterojunction solar cell fabricated withJK216D :PC71 BM (optimized weight ratio of 1 : 2 and processed with CB) exhibited a PCE of 3.60% ( J sc = 9.97 mA cm −2, V oc = 0.86 V and FF = 0.42). The PCE has been further improved up to 5.25% ( J sc = 11.86 mA cm −2, V oc = 0.82 V and FF = 0.54), when the optimizedJK216D :PC71 BM (1 : 2) active layer was processed with the addition of 3 v% 1, 8-diiodoctane (DIO) into the CB solution.